2003
DOI: 10.1016/s0002-9440(10)63850-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultraviolet Irradiation and Heparin-Binding Epidermal Growth Factor-Like Growth Factor in the Pathogenesis of Pterygium

Abstract: Ultraviolet (UV) light is one of the major factors implicated in the pathogenesis of pterygium. The mechanism by which UV light induces this disease remains elusive. The aim of this study was to evaluate the effects of UVB irradiation on the expression of growth factors in cultured pterygium epithelial cells and to demonstrate their distribution within pterygium. We cultured pterygial epithelial cells from pterygium explants and these cells were exposed to 20 mJ/cm 2 of UVB. Total RNA was extracted at 0, 6, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
62
1
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 47 publications
2
62
1
3
Order By: Relevance
“…Using a pterygium-derived epithelial cell culture model, we demonstrated the partial involvement of the EGFR in transmitting an extracellular UVB signal that resulted in the activation of an intracellular signal transduction pathway. Interestingly, the same molecules and pathways were not activated by UVB in normal conjunctival or limbal 8 epithelial cells and this observation is currently under investigation in our laboratory.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Using a pterygium-derived epithelial cell culture model, we demonstrated the partial involvement of the EGFR in transmitting an extracellular UVB signal that resulted in the activation of an intracellular signal transduction pathway. Interestingly, the same molecules and pathways were not activated by UVB in normal conjunctival or limbal 8 epithelial cells and this observation is currently under investigation in our laboratory.…”
mentioning
confidence: 66%
“…6 Recently, we have identified UVB as an environmental agent likely to be responsible for initiating molecular events that lead to the formation of pterygia. 7,8 From our hypothesis, 9 we postulate that UVB radiation activates cells at or near the limbus. This activation may cause 1) phenotypic alterations in a distinct population of epithelial cells, 2) production of proinflammatory and angiogenic cytokines 7 and growth factors, 8 and 3) increased invasiveness due to enhanced production of matrix metalloproteinases (MMPs) over and above their natural tissue inhibitors (TIMPs).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Among these risk factors, UV exposure has been documented to have strong correlation with pterygium, but the mechanism by which UV light induces pterygium remains elusive. Nolan et al 15 demonstrated that heparin-binding epidermal growth factor-like growth factor, a potent mitogen, was localized in pterygium tissue, and was significantly induced by UVB in pterygium-derived epithelial cells. Lu et al 16 has proposed photo-damage in pterygium from the point of view of lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%